ANALISIS KREATIVITAS GURU DAN GAYA BELAJAR SISWA DITINJAU DARI PEMAHAMAN KONSEP MATEMATIKA SISWA SMP - Hadi Harianto; Andini Dwi Rachmawaty (MES: Journal of Mathematics Education and Science, 2021)
This study aims to analyze the creativity of teachers and students 'learning styles on students' understanding of mathematical concepts. Teacher creativity when managing the classroom greatly affects the development of students' mathematical conception. This type of research used in this research is qualitative research with qualitative descriptive methods. This research was conducted at SMP Muhammadiyah 9 Surabaya. Data collection techniques used in this study were tests and questionnaires. Data analysis performed in this study was data reduction, data presentation, and conclusion drawing. The validity of the data used was triangulation of data, namely by checking or comparing the data obtained from the concept comprehension ability test, learning readiness questionnaire based on learning styles. Based on the results of the study it can be concluded that the learning styles of class VII students of SMP Muhammadiyah 9 Surabaya are dominated by visual learning styles as many as 25 students, followed by 4 students with auditory learning styles and 1 student with kinesthetic learning styles.